LEARNING ASSESSMENT IN THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM - Kaharuddin (Publikasi dan UKI Press UKI Toraja., 2024)
History learning includes three activities, namely planning, implementation and assessment. However, history teachers tend to be more concerned with planning and implementation, while the assessment aspect is considered less important. In the Kurikulum Merdeka, assessment is an activity that is as important as learning, even the official guidelines are entitled